KONSERVATISMA AKUNTANSI DAN SENGKETA PAJAK PENGAHASILAN (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di BEI) (Students' Journal of Accounting and Banking, 2012)
Problems in this study is whether the accounting conservatism effect on income tax disputes, as measured by the ratio of accounts receivable based on accounts payable, cash inflows to cash outflows, and the sale of the cost.The population in this study is a manufacturing company that went public and listed on the Stock Exchange. The sample used was 55 manufacturing companies. Type of data used was secondary data of every manufacturing company listed on the Indonesia Stock Exchange for three years ie 2009, 2010 and 2011. Data analysis technique used is multiple linear regression.The results of this study can be concluded that: (1) accounting conservatism affects the income tax disputes as measured by the ratio of accounts receivable to accounts payable (AR / AP). (2) The conservatism of accounting does not affect the income tax disputes as measured by the ratio of cash receipts to cash disbursements (CR / CD). (3) accounting conservatism affects the income tax disputes as measured by the ratio of the cost of sales (sales / exp).Keywords: konservatisma and income tax disputes